Training in tools to develop Quantitative Risk Assessment using Spanish ready‐to‐eat food examples. (26th November 2020) - ; Georgalis, Leonidas; Garre, Alberto; Fernandez Escamez, Pablo S
Abstract: Unsafe food poses global health threats, potentially endangering consumers. The great majority of people will experience a food‐borne disease at some point in their lives. Ready‐to‐eat (RTE) food is the one intended by the producer or the manufacturer for direct human consumption without the need for cooking or other processing effective to eliminate or reduce the concentration of pathogenic microorganisms. Prepared foods are often complex and may contain multiple components that make them vulnerable for growth of pathogenic microorganisms. Among all the pathogenic microorganisms that may be present in RTE foods, Listeria monocytogenes is of special interest because it is the causative agent of listeriosis and it has the ability to survive and replicate at refrigeration and low pH conditions. We performed a quantitative microbial risk assessment (QMRA) in RTE dry‐fermented sausage to measure the risk of listeriosis associated to the consumption of this product. The starting point of our investigation was the storage at the factory, after the end‐product was produced and before distribution to retail. The stochastic model was implemented in MicroHibro, an online tool for QMRA. Because L. monocytogenes concentration and prevalence can vary greatly between different studies and different types of fermented sausages, we tested different scenarios to show the importance of low prevalence and concentration of the pathogen at the final product. Our results show that the risk estimates are very sensitive to the modelling hypotheses used to describe this process. Therefore, the development of accurate probabilistic models describing the initial concentration of L. monocytogenes shall largely reduce the uncertainty associated to the QMRA of listeriosis in this type of product.